2017
DOI: 10.3920/jiff2016.0033
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices on edible insects in Lango sub-region, northern Uganda

Abstract: The study was done to determine the knowledge, attitude and practices towards edible insects, their consumption and practices of harvesting and processing in Lango sub-region, with the aim of increasing their consumption and improving nutrition of the people. Data was collected using semi structured questionnaires and focus group discussions. Common insect orders used as food in the area included: Isoptera (termites), Orthoptera (grasshoppers, crickets), and Hymenoptera (honey bee broods). Winged termites (Mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 18 publications
5
35
0
Order By: Relevance
“…Although consumption of edible insects is widespread in Uganda, the type of edible insects consumed varies between the different regions and cultures. For instance, the Bantu ethnic group, who occupies the central region of Uganda predominantly consumes grasshoppers (Agea et al 2008), while the Nilotics (who occupy the northern region) majorly consumes termites and their alates (Akullo et al 2017). The study of Akullo et al (2017), conducted in Lango sub-region of Northern Uganda showed that over 90% of the participants consumed white ants, a finding that compares well with results from the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although consumption of edible insects is widespread in Uganda, the type of edible insects consumed varies between the different regions and cultures. For instance, the Bantu ethnic group, who occupies the central region of Uganda predominantly consumes grasshoppers (Agea et al 2008), while the Nilotics (who occupy the northern region) majorly consumes termites and their alates (Akullo et al 2017). The study of Akullo et al (2017), conducted in Lango sub-region of Northern Uganda showed that over 90% of the participants consumed white ants, a finding that compares well with results from the current study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Bantu ethnic group, who occupies the central region of Uganda predominantly consumes grasshoppers (Agea et al 2008), while the Nilotics (who occupy the northern region) majorly consumes termites and their alates (Akullo et al 2017). The study of Akullo et al (2017), conducted in Lango sub-region of Northern Uganda showed that over 90% of the participants consumed white ants, a finding that compares well with results from the current study. This observation could explain the observed effect of location on consumption of insects and justifies the influence of culture and familiarity on edible insect consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, the poultry reared under the free-range system eat insects as they roam around homes and gardens and sometimes farmers deliberately avail the insects to their poultry. In Northern Uganda, farmers feed their chicken on insects by, for instance, digging up ant hills to expose termites or inserting grass blades into anthills to collect the termites (Akullo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, human consumption of edible insects (Entomophagy) has attracted a lot of attention and gaining popularity and acceptance in the world as a promising way to deal with some of the major food and nutrition challenges facing the world (Yen 2009;Yi et al, 2010;Durst et al, 2010;Mitsuhashi 2010;Ash et al, 2010;Vogel 2010;Gahukar 2011;Crabbe 2012;Vanhonacker et al, 2013;Van Huis et al, 2013;Sabado and Aguanta 2015;Narzari and Sarmah 2015;Megido et al, 2016;Akullo et al, 2017). Edible insects are traditionally consumed in many parts of the world (DeFoliart 1997;Ramos-Elorduy 2009) and considered as an important source of food (Belluco et al, 2013;Mlcek et al, 2014;Shockley and Dossey 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a reluctance to consume insects as food in some part of the world, there is an increasing interest in edible insects recently and they are now regarded as a class of mini-livestock (DeFoliart 1995;Hardouin 1995;Paoletti 2005;Morris 2008;Van Huis et al, 2013;Kenis et al, 2014;Kelemu et al, 2015). Many researchers around the world are looking for ways to include them in their daily diet and are investigating public attitude towards edible insects (Ebenebe and Okpoko 2015;House 2016;Niassy and Ekesi 2016;Anankware et al, 2017;Akullo et al, 2017). The objective of this study is to determine the attitudes of the young generation in Erciyes University towards entomophagy and the reasons for rejecting entomophagy.…”
Section: Introductionmentioning
confidence: 99%